2022
DOI: 10.1177/14644207221129292
|View full text |Cite
|
Sign up to set email alerts
|

Calotropis gigantea stem fiber reinforced thermoset plastics: Interlaminar shear strength and related tribo-mechanical properties

Abstract: This study examines the effects of lignite fly ash as a filler on the tribological and mechanical performance of a Calotropis gigantea fiber–epoxy composite. The investigation results show that the Calotropis gigantea fiber/epoxy composite with 2 wt.% lignite fly ash nanofiller added had better tensile strength, interlaminar shear, impact strength, and flexural strength than the control sample by 29.83%, 58.17%, 69.16%, and 11.41%, respectively. The manufactured composite samples were subjected to tribological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The elongation at break decreased with increasing filler loading, possibly because the fillermatrix contact became less deformable (Neitzel et al 2011). The addition of silicon carbide particles to A. catechu fiber epoxy composites influenced the samples' flexural strength (Ashok et al 2023). In particular, the flexural strength of samples S4, S5, and S6 containing 10% silicon carbide was lower than that of samples without silicon carbide.…”
Section: Resultsmentioning
confidence: 99%
“…The elongation at break decreased with increasing filler loading, possibly because the fillermatrix contact became less deformable (Neitzel et al 2011). The addition of silicon carbide particles to A. catechu fiber epoxy composites influenced the samples' flexural strength (Ashok et al 2023). In particular, the flexural strength of samples S4, S5, and S6 containing 10% silicon carbide was lower than that of samples without silicon carbide.…”
Section: Resultsmentioning
confidence: 99%
“…This may be because of the increase in filler, resulting in more particle‐to‐particle interface rather than nanoparticles interacting with the TF and matrix. Ashok et al 37 conducted a study on the impact of adding lignite fly ash to calotropis gigantea stem fiber epoxy composites. They found that the optimal quantity of nanoparticles led to an increase in shear strength.…”
Section: Resultsmentioning
confidence: 99%
“…This may be because of the increase in filler, resulting in more particle-to-particle interface rather than nanoparticles interacting with the TF and matrix. Ashok et al 37 conducted a study on the impact of adding lignite fly ash to…”
Section: Ilss Testmentioning
confidence: 99%